Methylprednisolone Pulses Plus Tacrolimus in Addition to Standard of Care vs. Standard of Care Alone in Patients With Severe COVID-19. A Randomized Controlled Trial - Solanich, Xavier; Antolí, Arnau; Rocamora-Blanch, Gemma; Padullés, Núria; Fanlo-Maresma, Marta; Iriarte, Adriana; Mitjavila, Francesca; Capdevila, Olga; Riera-Mestre, Antoni; Bas, Jordi; Vicens-Zygmunt, Vanesa; Niubó, Jordi; et al. (Frontiers in Medicine, 2021)
Introduction Some COVID-19 patients evolve to severe lung injury triggered by both the coronavirus infection and the subsequent host-immune response. Methods We conducted a randomized, open-label, single-center, phase II trial to evaluate the efficacy and safety of methylprednisolone pulses and tacrolimus plus standard of care (SoC) versus SoC alone, in hospitalized patients with severe COVID-19. The primary outcome was time to clinical stability within 56 days after randomization. Trial registration number: NCT04341038/EudraCT: 2020-001445-39. Results From April 1 to May 2, 2020, 55 patients were prospectively included for subsequent randomization; 27 were assigned to the experimental group and 28 to the control group. The experimental treatment was not associated with a difference in time to clinical stability (hazard ratio 0.73 [95% CI 0.39–1.37]) nor most secondary outcomes. Median methylprednisolone cumulative doses were significantly lower (360 mg [IQR 360–842] vs. 870 mg [IQR 364–1451]; p=0.007), and administered for a shorter time (median of 4.00 days [3.00–17.5] vs. 18.5 days [3.00–53.2]; p=0.011) in the experimental group than in the control group. Although not statistically significant, those receiving the experimental therapy showed a numerically lower all-cause mortality than those receiving SoC, especially at day 10 (2 [7.41%] vs. 5 [17.9%]; OR 0.39 [95% CI 0.05–2.1] ; p=0.282). The total number of non-serious adverse events was 42 in each the two groups. Those receiving experimental treatment had a numerically higher rate of non-serious infectious adverse events (16 [38%] vs. 10 [24%]) and serious infectious adverse events (7 [35%] vs. 3 [23%]) than those receiving SoC. Conclusions The combined use of methylprednisolone pulses plus tacrolimus, in addition to the SoC, did not significantly improve the time to clinical stability or other secondary outcomes compared with the SoC alone in severe COVID-19. Although not statistically significant, patients receiving the experimental therapy had numerically lower all-cause mortality than those receiving SoC, supporting recent non-randomized studies with calcineurin inhibitors. It is noteworthy that the present trial had a limited sample size and several other limitations. Therefore, further RCTs should be done to assess the efficacy and safety of tacrolimus to tackle the inflammatory stages of COVID-19.